Land Ownership and Tax System in the Kingdom of Temurids (Eurasian Journal of History, Geography and Economics, 2022)
The article analyzes the relations of land ownership in the Kingdom of Temurids, Tax Policy, their structure and systems, land ownership and tax policy, which have been formed since ancient times, on the basis of scientific sources.